GENOTYPE BY ENVIRONMENT INTERACTION AND GGE BIPLOT ANALYSES IN DURUM WHEAT UNDER WATERLOGGING STRESS - M. Tiryakioglu; C. T. Akçalı; C. B. Şahin; S. Karanlık; N. Ergün (Journal of Animal and Plant Sciences, 2023)
Waterlogging is one of the major limitations that reduce productivity in wheat all over the world. The present study aimed to identify waterlogging-tolerance in durum wheat genotypes. Thirty-two durum wheat genotypes were screened under aerobic and anaerobic conditions using randomized complete block design with three replications.High-purity nitrogen gas was used to provide and maintain waterlogging stress, while the control group was aerated with the air. Growth and physiological parameters i.e., shoot dry weight gain, root dry weight gain, total dry biomass weight gain, plant leaf area, dry leaf weight, specific leaf weight, chlorophyll content, carotenoid content, and their tolerance indices were determined. Durum wheat seedlings grown under anaerobic conditions had significantly lower shoot dry weight, total dry biomass weight, specific leaf weight, chlorophyll a, and chlorophyll a + b content. Results further revealed that the tolerance indices varied depending on wheat cultivars for the investigated parameters. Harran 95 under aerobic condition and Eminbey under anaerobic condition had the highest tolerance indices for shoot dry weight gain and total dry biomass weight gain. However, Kızıltan 91 had the highest tolerance indices for root dry weight gain under these two conditions. For these reasons, Kızıltan 91 came to forefront position with its stability and could be used in durum wheat breeding. For identifying the correlation of tolerance index with seed yield and potential genotypes to be used as a selection criterion, further studies are needed under field conditions.
Keywords: Waterlogging; aerobic and anaerobic conditions; genotype by environment interaction; GGE biplot analysis; durum wheat